Research into the energy conversion processes in hybrid plasma devices for applying the coatings - Pashchenko, Valeriy (Eastern-European Journal of Enterprise Technologies, 2017)
We investigated the processes of transformation of the incoming energy flows into thermal energy of the jet in the arc channel of plasma generator. As the plasma-forming gases, we used the mixtures of air with hydrocarbon gases. It is demonstrated that plasma generators that employ such gas mixtures have two channels for the introduction of energy (the energy of electric arc and the energy of combustion products of combustible gas in the oxidizer) and can be categorized as hybrid devices. The fact of mutual influence of the sources of energy, which is introduced, is proven. Transition to a more complex gas system increases the power of electric arc that burns inside it. Experimentally confirmed is the practical possibility to shift the region of combustion of the components of gas mixture beyond the limits of the arc channel of plasma generator. We established effect of the content of combustible component of the original mixture on the magnitude of energy share that is released outside the plasmatron in the plasma jet. The possibilities to control total capacity of the device and its specific energy characteristics by changing operational parameters of plasma generation are estimated. We established a leading role of the composition of original plasma-forming mixture in this process.